HDX-MS and MD Simulations Provide Evidence for Stabilization of the IgG1—FcγRIa (CD64a) Immune Complex Through Intermolecular Glycoprotein Bonds. Issue 2 (30th January 2022) - Anderson, Kyle W.; Bergonzo, Christina; Scott, Kerry; Karageorgos, Ioannis L.; Gallagher, Elyssia S.; Tayi, Venkata S.; Butler, Michael; Hudgens, Jeffrey W.
Graphical abstract: Highlights: Previous studies present discordant models of Fc—FcγRI complex stabilization. HDX-MS of IgG1—FcγRI complexes infers presence of intermolecular glycoprotein bonds. Simulations evince glycoprotein bonds within the Fc and between the Fc and FcγRI. Bonds between Fc glycans and the FG-loop of FcγRI contribute to IgG1—FcγRI binding. Abstract: Previous reports present different models for the stabilization of the Fc—FcγRI immune complex. Although accord exists on the importance of L235 in IgG1 and some hydrophobic contacts for complex stabilization, discord exists regarding the existence of stabilizing glycoprotein contacts between glycans of IgG1 and a conserved FG-loop ( 171 MGKHRY 176 ) of FcγRIa. Complexes formed from the FcγRIa receptor and IgG1s containing biantennary glycans with N-acetylglucosamine, galactose, and α2, 6-N-acetylneuraminic terminations were measured by hydrogen–deuterium exchange mass spectrometry (HDX-MS), classified for dissimilarity with Welch's ANOVA and Games-Howell post hoc procedures, and modeled with molecular dynamics (MD) simulations. For each glycoform of the IgG1—FcγRIa complex peptic peptides of Fab, Fc and FcγRIa report distinct H/D exchange rates. MD simulations corroborate the differences in the peptide deuterium content through calculation of the percent of time that transient glycan-peptide bonds exist. These results indicate that stability of IgG1—FcγRIa complexes correlate with the presence of intermolecular glycoprotein interactions between the IgG1 glycans and the 173 KHR 175 motif within the FG-loop of FcγRIa. The results also indicate that intramolecular glycan-protein bonds stabilize the Fc region in isolated and complexed IgG1. Moreover, HDX-MS data evince that the Fab domain has glycan-protein binding contacts within the IgG1—FcγRI complex.